THE IMPACT OF STRATEGIC VIGILANCE IN HIGH PERFORMANCE APPLIED RESEARCH IN COMMUNICATION COMPANIES (ASIA CELL, CORK TELECOM) - Mahmood Ayyed Hasan (Scholar Express Journal, 2022)
The current research aims to test the impact of strategic vigilance in high performance in communication companies, and for this the researcher selected a random sample that included (120) leaders of communication companies Asia Seal Cork Telecom (executive director, assistant manager, department head, division officer), distributed to them the main research tool to survey opinions on the variables researched, recovered (110) of them, while the valid ones for statistical analysis (100) views, Statistical analysis has shown a number of results, most notably the interest of communication companies in strategic vigilance and high performance, as well as the fact that telecommunications companies have been able to improve their ability to perform highly by employing their strategic vigilance.
Keywords: Strategic vigilanc; high performance; communication companies